PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) BERBASIS STEM PADA MATERI SUB KONSEP PERUBAHAN LINGKUNGAN TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS X SMAN 11 BANJARMASIN - Husain, Naufal Shadiq; Noorhidayati, Noorhidayati; Utami, Nurul Hidayati (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2024)
One form of learning in implementing the Merdeka curriculum is the application of the PBL-STEM model which brings students closer to real problems. The aim of this research is to examine the effect of applying the PBL-STEM model on cognitive learning outcomes in the environmental change sub-concept material. The method used in this research was quasi-experimental and non-equivalent control group. The experimental class was held in class X-F with a minimum number of students 34 people, and the control class was held in class X-D with a minimum number of students 34 people. Data was collected from pretest and posttest scores (product cognitive). In the data analysis technique, the Wilcoxon test was used for pre-test and post-test. The results of the research show that the application of the PBL STEM model has an effect on students' cognitive learning in learning the sub concept of environmental change in class X, 7.03 (caring), 6.78 (sharing), and psychomotor 21.2 (high category).